INOVASI PROSES LAYANAN ADMINISTRASI PELANGGAN MELALUI PENERAPAN SISTEM ANTRIAN DAN MANAJEMEN WAKTU - Ahmad Jet Alamin A; Parlaban Karo-Karo; Robintang Elfrianto Naibaho (Jurnal Industri Kreatif dan Inovatif, 2025)
This Community Service Program aims to improve the efficiency of managing community projects by applying Agile project management methods tailored to volunteer-based settings. The partner’s main issues include inflexible and less adaptive planning, unclear task assignment, changing needs during implementation, delays in progress, and inconsistent reporting documentation. The intervention consists of process assessment, practical Agile training, implementing simple working tools (Kanban board, backlog, sprint planning, daily/weekly check-ins), and ongoing implementation assistance for selected community projects. The outputs include a concise Agile community SOP, backlog and Kanban templates, sprint reports, and a performance indicator dashboard. The expected outcomes are improved milestone timeliness, better volunteer coordination, increased progress transparency, and improved quality of activity reporting.